Deciphering the Shifts in Microbial Community Diversity From Material Pretreatment to Saccharification Process of Fuyu-Flavor Baijiu - Kang, Jiamu; Hu, Yunan; Ding, Ziyuan; Ye, Li; Li, Haoran; Cheng, Jun; Fan, Lin; Zhao, Hu; Han, Beizhong; Zheng, Xiaowei (Frontiers in Microbiology, 2021)
The microbiota of the pretreatment phase is crucial to the assembly of the microbial community in the saccharification of Fuyu-flavor Baijiu. This study investigated the shifts in microbial community diversity from the pretreatment of raw materials to the end of saccharification. High-throughput sequencing revealed that Lactobacillus, Weissella, and Bacillus in the bacterial community and Rhizopus, Candida, Pichia, and Aspergillus in the fungal community were predominant during raw materials pretreatment and saccharification processes. Also, eleven bacterial genera including Bacillus, Lactobacillus, Leuconostoc, Weissella, Lactococcus, and Acetobacter and eight yeast genera including Candida, Pichia, Saccharomyces, and Wickerhamomyces were isolated from the initial saccharification stage by culture-dependent approaches. Sourcetracker analysis indicated that the cooling grains and rice husks were the main contributors to the bacterial community composition of the saccharification process, and Qu was the main contributor to the shaping of the fungal community structure during the saccharification process. Abundance variation of the predictive functional profiles of microbial communities encoding for key enzymes involved in pyruvate metabolism, starch and sucrose metabolism, and glycolysis/gluconeogenesis during pretreatment and saccharification phase were inferred by PICRUSt2 analysis. The results of this study will be utilized to produce consistently high-quality Fuyu-flavor Baijiu via better controlling the shaping of microbial community structures during pretreatment and fermentation processes.